‘Othering’ Adivasi Identities: Perpetuating Tribal Stereotypes among the Bhil of India - Tandon, Indrakshi (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2021)
Focusing on the indigenous Bhil community in central India, this paper examines the role of British colonial policies in paving the way for ‘tribal identity’ formation and, how postcoloniality, or the postcolonial condition, is continuing to shape this identity. I interrogate the power of the colonial and contemporary government to categorize, and how such categories persist in the consciousness of the Indian government, mainstream communities, and more significantly, among indigenous communities themselves. Modernizing and developing the Bhil (among other indigenous communities) has been a national goal for the nation-state since independence. According to Indian development policies, building an agrarian community that is self-sufficient and empowered is in the best interest of the nation and its economic growth. I argue that far from portraying a unified national identity to demonstrate modernity and progress to the world, Indian policies have instead created politicized identities, which serve to perpetuate stereotypes and contain their subjects in exploitative cycles of debt, dependency, and development.